Trade effects of the euro: evidence from sectoral data - Richard E. Baldwin; Frauke Skudelny; Daria Taglioni (European Central Bank (ECB), 2005)
This paper contributes to the literature on the impact of EMU on trade, adding two new elements. First, we propose a theoretical model for explaining how the euro could have increased trade by the large amounts found in the empirical literature. Second, we propose a sectoral dataset to test the insights from the theory. Our theoretical model shows that in a monopolistic competition set-up, the effect of exchange rate uncertainty on trade has nonlinear features, suggesting that EMU and a standard measure for exchange rate uncertainty should be jointly significant. Our empirical results confirm this finding, with a trade creating effect between 108 and 140% in a pooled regression, and between 54 to 88% when sectors are estimated individually. Importantly, we find evidence for a trade creating effect also for trade with third countries.
Keywords: F12; C33; E0; 330; Exchange rate volatility; gravity; monetary union; Rose effect; sectoral trade; Eurozone; Wohlfahrtsanalyse; Internationale Wirtschaft; Handelseffekt; Risiko; Wechselkurs; EU-Staaten